Instagram photography and the geography field course: snapshots from Berlin. Issue 3 (3rd July 2019) - Davies, Thom; Lorne, Colin; Sealey-Huggins, Leon
ABSTRACT: Although geography has long associated itself with photography, the rapid advancement of technology has created a clear divide between the visual practices regularly used in wider society and the way photography is utilized by critical geographers in their teaching. We suggest the door is ajar for new modes of (geo)photographic thinking, and one visual tool at our disposal is social media applications that allow images to be instantly shared, analysed, and discussed. This article critically reflects on the use of Instagram to enhance student participation, engagement, and learning on a geography field course in Berlin. Based on interviews with students, their field journals, and our own critical reflections, this paper looks at some advantages of using Instagram in teaching geography, but also promotes caution and presents drawbacks to relying on instant visual digital methods.